NILAI BUDAYA DAN FUNGSI SOSIAL LEGENDA RATU PUTRI KENANGA DI NAGARI SINGKARAK KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Syukri, Muthia Rahmi; Hayati, Yenni; Nst., Muhammad Ismail (Universitas Negeri Padang, 2018)
This study aims to describe: (1) the legend values of Queen Putri Kenanga in Nagari Singkarak Subdistrict X Koto Singkarak Solok Regency, (2) the social function of legend of Queen Putri Kenanga in Nagari Singkarak Subdistrict X Koto Singkarak Solok Regency. This research type is qualitative research by using descriptive method. Data were collected through interviews, recording, transcription, transliteration, and classification by recording interviews with informants in Nagari Singkarak Subdistrict X Koto Singkarak Solok Regency.Â Data analysis were carried out with the following steps. First, Analyze. Second, Interpret data.Third,Inventory. Fourth, make a conclusion based on the results of research. Based on the result of research, itâ€™s concluded the following matters. First, the values of QueenPutri Kenanga in Nagari Singkarak Subdistrict X Koto Singkarak Solok Regency.The cultural values contained in the legend of Queen Putri Kenanga were summarized in conflicts that occur in the five patterns of human relationships, namely: (a) human relationships with creators, (b) human relationships with nature, (c) human relationships with society, (d) human relationships with other human beings, and (e) human relationships with oneself.Based on this research, it can be concluded that Nagari Singkarak has high humanitarian values. Second, the socialfunction of the legend of Queen PutriKenanga is as a function of educating, bequeath, identity, entertaining and tradition.Keywords: cultural value, social function, legend, Queen Putri Kenanga